Élites éclairées et intellectuels progressistes grecs dans l’Alexandrie de Cavafy - Sophie Coavoux (Cahiers Balkaniques)
In the early Twentieth century, Alexandria is one of the most prestigious centres of Hellenism. If the Greeks held a key role in trade and commerce, industry, banking, they also distinguished themselves in the realm of arts, literature and ideas. One of the specificities of Alexandrian Greek elites lies in a certain propensity to avant-garde and progressive trends, both aesthetic and ideological or political. On the one hand, the “organic intellectuals” seem to embody a Hellenocentric, nationalist, Helladic model. As for the left-wing intellectuals, far from adopting a strictly Hellenocentric posture, they opt for a more European, cosmopolitan, Panhellenic vision.